An integrative approach to reappraising species validity in Pseudexostoma (Teleostei: Sisoridae) - Yang, Kunfeng; Jiang, Wansheng; Chen, Xiaoyong; Zhou, Wei; Yang, Junxing (Zootaxa, 2016)
The catfish genus Pseudexostoma (Sisoridae) currently contains three species: P. yunnanensis from the upper Irrawaddy River (Dayingjiang), and P. brachysoma and P. longipterus from the upper Salween River (Nujiang). We adopted an integrative approach combining both morphology-based (traditional measurements, truss-based and geometric morphometrics, fin skeleton examination and X-ray photography) and molecular approaches (genetic distances, haplotype network, phylogenetic relationships) to reappraise species validity in Pseudexostoma. Our results showed that P. longipterus cannot be distinguished from P. brachysoma from either morphological or molecular analyses, and that the former name should thus be considered a junior synonym of the latter. The two remaining geographically isolated species, P. yunnanensis and P. brachysoma, showed a distinct genetic distance equated to the typical 2% sequence divergence threshold delineating different species of fishes, and with a divergence time dated to approximately 1.22–2.14 million years ago. Although P. yunnanensis and P. brachysoma share some morphological characters that appear gradually diverging (body depth at anus and interorbital distance), some degree of overlap still exists, we suggest the two species are distinct based on the total evidence.